Analysis and Design of Monitoring Information System in the General Affairs Division - Charles Liustanto; Verri Kuswanto (bit-Tech, 2025)
With the rapid advancement of technology, the surrounding environment must adapt to these developments. This can be seen in the industrial sector, which is starting to adopt information systems to support its activities. However, this adaptation is not uniform, and some areas have yet to adopt information systems to support their operations, such as at PT. Diansurya Global, particularly in the General Affairs Division. In this division, all activities are conducted traditionally, such as managing vehicle orders, monitoring the availability of drivers and vehicles, and storing vehicle data, which is still in hardcopy format. Therefore, a monitoring information system is needed to assist the activities in the General Affairs Division. PT. Diansurya Global is a company that produces and exports metal equipment. Consequently, a monitoring information system is designed to provide real-time information on the availability of drivers and vehicles, which accelerates the determination of routes and delivery schedules. Additionally, this system can also assist other divisions in placing operational vehicle orders, thus preventing duplicate or uncommunicated orders due to the documentation within the system. System testing is conducted using the user acceptance testing method to ensure that the features meet user needs. This monitoring information system can also be used to store information such as vehicle administration data, including payment history for administrative costs and maintenance history for operational vehicles.